A simplified mode diversity coherent receiver based on non-mode-selective photonic lantern and Kramers-Kronig detection. (June 2023) - Qiu, Cong; Ma, Wenqi; Liu, Feng; Hu, Guijun
Highlights: A mode diversity KK coherent receiver system is proposed that can effectively compensate for atmospheric turbulence. The system is more suitable for long-range space laser communications of 2–16 km. The system is simpler, smaller and less powerful, compared to balanced detection based on mode diversity. Abstract: This paper proposes a mode-diversity space optical communication receiver for long-range space optical communication, which can compensate for the effect of atmospheric turbulence and be applied between 2 km and 16 km space optical communication with a low-cost, low-power and low-complexity feature. The receiver uses a non-mode selective photonic lantern as a mode demultiplexer, merging using an equal gain combining (EGC) algorithm and a Kramers-Kronig (KK) detection technique to accomplish the optical detection of high-dimensional modulated format signals. The performance of the receiver under different turbulent conditions is experimentally investigated, showing significant compensation for atmospheric turbulence. The experimental results show that the proposed scheme achieves a gain of 4–5 dB at BER = 3 × 10 −3 compared to a single-mode fiber (SMF) receiver under moderately strong turbulent conditions.